PENGARUH KEPEMIMPINAN DAN KOMPETENSI PENGURUS TERHADAP KEUNGGULAN BERSAING (Studi Pada Lembaga Perkreditan Desa Di Kabupaten Buleleng Bali) - Ketut Gunawan (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
The competitiveness ability of Village Credit Institutions or Lembaga Perkreditan Desa (LPD) in Buleleng Regency on average decreased during 2018, 2019 and 2020. Leadership and human resource competencies play an important role in achieving competitive advantage. This study aims to determine the influence of leadership and human resource competence on the competitive advantage of LPD in Buleleng Regency partially and simultaneously. The leadership variable adopts the eight leadership traits of Asta Brata which include: indra brata, yama brata, solar brata, candra brata, vayu brata, bhumi brata, varuna brata and kwera brata. Human resource competencies include: knowledge, skills and abilities. Competitive advantages include: the threat of new entrants, the supply power of suppliers, the supply power of buyers, the threat of substitute products, and competition. Data were collected using a questionnaire technique that has been tested for validity and reliability and analyzed by regression analysis and moderated regression analysis. The results of data analysis indicate that leadership has a positive and significant effect on competitive advantage, and human resource competence strengthens the influence of leadership on LPD competitive advantage in Buleleng Regency, Bali.